Hubungan Peran Orang Tua Mengenai Jajanan Sehat Dengan Sikap Dan Kebiasaan Jajan Anak Di SD Negeri Kalasey Kecamatan Pineleng - Tamanampo, Kezia; Renteng, Septriani; Simak, Valen Fridolin (Mapalus Nursing Science Journal, 2023)
Background: Children's snacking behavior is influenced by environmental factors because children cannot distinguish between healthy and unhealthy snacks. Environmental s that are very influential in children's snacking behavior is the role of parents. The purpose: This study aims to analyze the relationship between the role of parents regarding healthy snacks and the attitudes and eating habits of school-age children. Methods: Analytical research design with quantitative methods with a cross sectional approach. The sample consists of 123 respondents with the sampling method using the Probability Sampling approach with the Stratified Random Sampling method. Results: Using the Chi Square test with a degree of confidence of 95% shows the role of parents regarding healthy snacks with a snacking attitude has a p value of 0.347> 0.05 and the role of parents regarding healthy snacks with children's snacking habits has a p value of 0.118> 0.05 . Discussion:: The role of parents is influenced by the knowledge gained, snacking attitude are influenced by experiences experienced, and children’s snacking habits are influenced by the availability of snacks and pocket money earned.. Conclusion: Based on the results of the study, it can be concluded that the role of parents regarding healthy snacks and the attitude of children's snacks and the role of parents regarding healthy snacks and children's snacking habits has no relationship. Keyword: Parents role, healthy snacks, school-age children